A qualitative study of the experience of primary caregivers of patients receiving end of life hospice care - Lubbe, Johanne (Department of Public Health and Family Medicine, 2023)
Introduction. A life-threatening illness impacts profoundly not only the patient but also the family. As the spouse or partner is often the primary caregiver for patients with a life-threatening illness it especially affects the couple as a unit, rather than isolated individuals. The Aim of this study. To explore and describe and describe the experience of primary caregivers of patients at end of life receiving care from Hospice Bloemfontein. Objectives. 1. To obtain an in-depth description of the experience of primary caregivers of patients within hospice care. 2. To explore and describe primary caregivers' coping mechanism while providing care. 3. To explore and describe support structures and resources that assist the primary caregiver. Methods. A qualitative study was conducted through individual semi-structured interviews, to explore the experiences of primary caregivers taking care of their partners with a life-limiting disease in hospice care in Bloemfontein, Free State. Results. The findings of this study reflect on the complex experiences and emotional responses of primary caregivers taking care of their partners with a life-limiting disease in hospice care. It also reflects on the demands that are placed on those caregivers to meet all the different and multidimensional needs of their ill partners, which include the effect it has on them financially, physically, and personally. The study further reflects on their emotional reaction to the illness, their caregiving and the impending death of their partners in a context where they are often isolated. Certain factors added to and others relieved caregivers' distress. Although there were common themes, the reactions and experiences of all participants were unique and individual. As a consequence of these demands some of the caregivers in the study experienced exhaustion, physical complaints, isolation, sleeplessness, spiritual distress, and unmet needs. Conclusions. This study reflects on the importance of the role of caregivers as an active participant in providing care and comfort during the final stages of the illness of a patient, but also reinforces the critical need to provide the necessary and adequate support to those caregivers. A thorough assessment is necessary to respond holistically to the unique and individual needs, challenges, and concerns of families.